2010
DOI: 10.4103/0019-509x.58857
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated non-Hodgkin′s lymphoma: Experience from a regional cancer center

Abstract: These NHL are of higher grade and advanced stage. Response and tolerance to chemotherapy is poor. Appropriate supportive care and CNS prophylaxis might improve outcome. We need to improve epidemiological data collection system in this part of world. With HAART, the goal of therapy is durable CR rather than palliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
(22 reference statements)
2
8
0
2
Order By: Relevance
“…12 out of the total 18 (66.7%) patients in present study had high grade B-cell NHL. Similar observation was made by Sharma et al [15] in their analysis of HIV-associated NHL.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…12 out of the total 18 (66.7%) patients in present study had high grade B-cell NHL. Similar observation was made by Sharma et al [15] in their analysis of HIV-associated NHL.…”
Section: Discussionsupporting
confidence: 88%
“…Over two-thirds (69%) of patients in their study were males. Sharma et al [15] in their analysis of 7 patients of HIV-associated NHL reported median age at the time of lymphoma diagnosis of 38.57 years (range 14-56 years). They also have reported male preponderance, with 5 out of the 7 patients in their study being males.…”
Section: Discussionmentioning
confidence: 99%
“…La edad mediana en esta serie fue de 39,5 años, lo cual es concordante con otros reportes 7,[18][19][20] . Por otra parte, existió un claro predominio de pacientes varones en este estudio, hecho que se ha atribuido a una mayor incidencia de infección por VIH en pacientes del género masculino [20][21][22][23] .…”
Section: Discussionunclassified
“…La edad mediana en esta serie fue de 39,5 años, lo cual es concordante con otros reportes 7,[18][19][20] . Por otra parte, existió un claro predominio de pacientes varones en este estudio, hecho que se ha atribuido a una mayor incidencia de infección por VIH en pacientes del género masculino [20][21][22][23] . En todos los casos el diagnóstico de linfoma se efectuó en etapa SIDA, con seis pacientes (42,8%) con recuentos de linfocitos CD4 < 50 céls/mm 3 , lo cual es compatible con el incremento del riesgo de ocurrencia de linfoma en estados de inmunodefi ciencia severa 2,8 .…”
Section: Discussionunclassified
“…Historically, patients with NHL and AIDS have been more likely to present with extranodal NHL and high grade histological findings, they have been less likely to respond to chemotherapy, with shorter overall survival [66]. Inappropriate treatment and inability to maintain dose density and intensity in the background of aggressive disease are determinants of poor response to therapy [67].…”
Section: Non-hodgkin Lymphoma (Nhl): Hiv-associated Non-hodgkin Lymphomamentioning
confidence: 99%